(untitled) (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2023)
In this article we present the modern trends like Explainable Machine Learning (EML) versus classical Machine Learning (ML), the computer security is to be evaluated from the point of view of the hashing and authentication schemes in Hyper-Text Transfer Protocol (HTTP), most of the emphasis of this work is made towards hashing in representing the identity of data sources and making possible to use these hashes as crypto currencies in block-chaining technology, the survey also gives the definition of the basic hashing algorithm in the assumption that P not equals NP, where P is the polynomial class of complexity and NP is a non-polynomial class, since this fact was proved before as equality between P and NP, this is still remains challenging to prove that hashing function can be dual for either input or output, thus giving the possibility of compromising the computer security system and obtain the prior hash in hashing queue in block-chaining and, probably, partial chunks of the hashed data.